2022
DOI: 10.7150/ijbs.70866
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between BEND5 and RBPJ suppresses breast cancer growth and metastasis via inhibiting Notch signaling

Abstract: High frequent metastasis is the major cause of breast cancer (BC) mortality among women. However, the molecular mechanisms underlying BC metastasis remain largely unknown. Here, we identified six hub BC metastasis driver genes (BEND5, HSD11B1, NEDD9, SAA2, SH2D2A and TNFSF4) through bioinformatics analysis, among which BEND5 is the most significant gene. Low BEND5 expression predicted advanced stage and shorter overall survival in BC patients. Functional experiments showed that BEND5 could suppress BC growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The first study of BEND5 was reported in colorectal cancer and showed the contribution of BEND5 hypermethylation to the proliferation of cells, marking its possibility as a prognostic marker ( 14 ). BEND5 has also been identified as a tumor suppressor gene associated with growth and metastasis in breast cancer ( 15 ). Our bioinformatics analysis showed that BEND5 is expressed at low levels in many cancer types, including colorectal and breast cancer, which is consistent with the findings reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The first study of BEND5 was reported in colorectal cancer and showed the contribution of BEND5 hypermethylation to the proliferation of cells, marking its possibility as a prognostic marker ( 14 ). BEND5 has also been identified as a tumor suppressor gene associated with growth and metastasis in breast cancer ( 15 ). Our bioinformatics analysis showed that BEND5 is expressed at low levels in many cancer types, including colorectal and breast cancer, which is consistent with the findings reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the early diagnosis and survival rates of patients with LUAD, specific major molecular pathways and multiple sensitive and reliable biomarkers need to be identified. The relationship between BEND5 and tumor development has been shown in earlier studies (14,15). However, an in-depth description of the role of BEND5 in LUAD is lacking.…”
Section: Investigating the Relationships Between Bend5 Expression And...mentioning
confidence: 91%
See 3 more Smart Citations